Why strict drug laws work (and why they do not) - Timothy A. Hickman (Amsterdam Law Forum, 2010)
<!--StartFragment--> Academic and scientific arguments in favour of the de-regulation of illicit drugs are usually made on the basis of the greater harm done by the laws than by the drugs themselves. This article argues that such claims miss a key point. They forget that drug policy is made for people from wealthy countries who do not and are not likely to take drugs. As such, arguments based on failed treatment programmes or on large-scale, organised drug crime often fall on the deaf ears of those who believe that strict drug laws help to keep them, and especially their children, off drugs. Advocates of drug de-regulation must take the interests and beliefs of this voting majority seriously if they wish to persuade politicians to ease their ‘war on drugs’. <!--EndFragment-->